IMPROVING THE ABILITY OF WRITING SIMPLE REPORTS THROUGH TRADITIONAL GAME TECHNIQUES IN STUDENTS - Dajani Suleman; Lian Pakaya (International Journal of Innovations in Engineering Research and Technology, 2020)
The results showed that out of 16 students of class II SDN 97 Sipatana, Gorontalo City, based on the results of preliminary observations, there were 3 students 19 % who were able to write simple reports, while the students who were not yet able were 13 students, 81%. In the first phase of the action cycle I, there were 4 students, 25% who were able and not capable, 12 students, 75%. In the second cycle, there were 5 students, 31% capable and 11 students, 69% in the second cycle, the capable students were 13 students, 81%, while the incapable students were 3 students, 19%. It is concluded that traditional playing techniques have improved the ability to write simple reports in grade II SDN 97 Sipatana, Gorontalo City.